Real‐Time Internal Steam Pop Detection during Radiofrequency Ablation with a Radiofrequency Ablation Needle Integrated with a Temperature and Pressure Sensor: Preclinical and Clinical Pilot Tests (Adv. Sci. 19/2021). Issue 19 (8th October 2021) - Park, Jaeho; Cha, Dong Ik; Jeong, Yongrok; Park, Hayan; Lee, Jinwoo; Kang, Tae Wook; Lim, Hyo Keun; Park, Inkyu
Abstract : Real‐Time Internal Steam Pop Detection Steam pop is one of the possible threats during radiofrequency ablation (RFA), a minimally invasive therapy to eliminate the cancer tissues. In order to monitor this threat, a flexible thinfilm type multimodal (pressure, temperature) sensor was integrated into the RFA needle, and successfully detected the steam pop in real‐time in a clinical demonstration. More details can be found in article number 2100725 by Hyo Keun Lim, Inkyu Park, and co‐workers.